2016
DOI: 10.1021/acs.iecr.5b04091
|View full text |Cite
|
Sign up to set email alerts
|

Studies on CO2 Adsorption and Desorption Properties from Various Types of Iron Oxides (FeO, Fe2O3, and Fe3O4)

Abstract: Various type iron oxides of FeO, Fe2O3, and Fe3O4 were used for carbon dioxide (CO2) capture at room temperature and pressure by studying its adsorption–desorption properties. Several interactions of carbonate species were detected on its surface. The morphology of carbonate formation shows different structures on FeO (grooves-like), Fe2O3 (fine sharp particles), and Fe3O4 (aggregated nanoparticles). CO2 chemisorption discovered a potential adsorbent of Fe2O3 with an adsorption capacity of 3.95 mgCO2/gadsorben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(56 citation statements)
references
References 40 publications
3
53
0
Order By: Relevance
“…[31,32,33,34] As the pH is decreased to 4.0 and to 3.9, a peak at 289.9 eV appears, indicating the presence of a surface bicarbonate (HCO 3 À ) species. [31][32][33]35] In addition, we observe a small feature at lower binding energy (281.5 eV) which is 8.4 eV apart from the main bicarbonate peak. This corresponds to the spacing between the α 1,2 and the α 3 lines of the Mg anode, and therefore the peak can be attributed to an x-ray satellite of the α 1,2 signal at 289.9 eV.…”
Section: Fe 3 O 4 (001): X-ray Photoelectron Spectroscopymentioning
confidence: 71%
“…[31,32,33,34] As the pH is decreased to 4.0 and to 3.9, a peak at 289.9 eV appears, indicating the presence of a surface bicarbonate (HCO 3 À ) species. [31][32][33]35] In addition, we observe a small feature at lower binding energy (281.5 eV) which is 8.4 eV apart from the main bicarbonate peak. This corresponds to the spacing between the α 1,2 and the α 3 lines of the Mg anode, and therefore the peak can be attributed to an x-ray satellite of the α 1,2 signal at 289.9 eV.…”
Section: Fe 3 O 4 (001): X-ray Photoelectron Spectroscopymentioning
confidence: 71%
“…Furthermore, density functional theory calculations have demonstrated that Fe 3 O 4 (111) surface is very capable of activating CO 2 (refs 20, 21). Typically, iron catalysts need alkali metal promotion to attain desired activity and selectivity.…”
mentioning
confidence: 99%
“…14 To date there are no investigations of CO 2 adsorption on well-defined iron-oxide surfaces, despite the important role of these materials in both geochemistry and catalysis. Work on polycrystalline Fe 3 O 4 , 15 Fe 3 O 4 nanoparticles, 16 and FeO x nanoclusters on graphite 17 suggests however that both physisorption and carbonate formation can a) E-mail address: parkinson@iap.tuwien.ac.at occur, with stronger binding linked to the presence of Fe 2+ cations. 18,19 Very recent density functional theory (DFT) calculations based on the Fe 3 O 4 (111) surface suggest that CO 2 chemisorption can occur at undercoordinated oxygen sites and that this surface can activate CO 2 for hydrogenation.…”
Section: Introductionmentioning
confidence: 99%